Percepções de mulheres que sobreviveram ao espectro da placenta acreta sobre a cesárea: o que dizem aquelas que optaram pela cesárea a pedido? - Begalli, Bruna Molina (Universidade Federal de São Carlos, 2024)
INTRODUCTION: The global increase in cesarean section rates has raised concerns about maternal morbidity and mortality associated with the procedure. Pregnant women's choice of method of delivery is influenced by personal and external factors, such as social, family and medical influences and pressures. Satisfaction with cesarean section, however, is often envied by studies that tend to present detailed opinions, making the results difficult to interpret. The growing preference for cesarean sections without medical indication raises doubts about the basis of these choices and the ability of women to critically evaluate medical recommendations, especially after serious complications. OBJECTIVE: The objective of this study was to evaluate the perceptions regarding cesarean section of women who, after having a cesarean section "on request", faced complications of the placental accreta spectrum (PAS). The responses of these women were compared to those of those who did not have this option. METHOD: This observational, retrospective and cross-sectional study was extended in a reference university hospital over 18 years (2005-2023). Included exposed women with PAS and undergoing postpartum hysterectomy. Data were collected via a structured questionnaire, complemented by information from medical records, covering demographics, perceptions about the first cesarean section and reflections after complications. Participants were divided into two groups: those with a cesarean section "on request" and those with a cesarean section on "other requests." The study was approved by the ethics committee. RESULTS: The study revealed that of the 66.7% participants who had three or more pregnancies, 36.4% were in the "on request" group and that 81.8% of these had private health insurance. Furthermore, 36.6% of women had little or no knowledge about the risks of cesarean section before the first surgery, and 85.4% were unaware of the PAS. More than half (53.7%) stated that they would make different decisions with current knowledge, and 78% believe that the public knows little about the topic. Finally, 19.6% disagree with the cesarean section law, and 31.7% were still unaware of the relationship between PAS and cesarean sections, even after a near miss. CONCLUSION: Cesarean section on request reflects a choice of a combination of several factors, influenced by beliefs and fears about vaginal birth, which is still seen as a convenient solution. Thus, the lack of knowledge about its risks and changes in opinion after serious complications reinforce that such choices are not based on scientific reflection. Therefore, for women's autonomy to be fully guaranteed, correct information and the deconstruction of deeply rooted myths among the population must be promoted.
Perceptions of women who survived the specter of placenta acreta about cesarean: what those who choose to have a cesarean on request say?
Keywords: Cesárea; Hemorragia pós-parto; Placenta acreta; Mortalidade materna; Cesarean section; Postpartum; Hemorrhage; Placenta accreta; Maternal mortality; CIENCIAS DA SAUDE::MEDICINA